Composite scintillators as new type of a scintillation material - Karavaeva, N.L. (Вопросы атомной науки и техники, 2014)
For radioecological tasks, we have developed a new type of scintillation materials - composite scintillators, consisting of dielectric gel as a base into which granules of scintillating substances were introduced. It has been shown that such material can be created both on the basis of organic and inorganic granules. In the first case, efficient fast neutron detectors can be created, with neutron discrimination on the background of gamma-radiation close to organic single crystals. In the second case, efficient detectors of thermal neutrons could be developed, with variation of the granule size allowing substantial reduction of the effects of background radiation. Separate fragments of the scintillator can be linked together, creating endless planes. A possibility of using bases with higher radiation hardness as compared with standard scintillator bases, as well as using any scintillating substance for granules allows thinking about possible application of such technological approach not only for radioecological tasks (ultra-low fluxes), but also in high energy physics.